KOMPOSISI MUSIK BATU NISAN KARYA F.X. SUTOPO Ditinjau Dari Aspek Rasa, Referensi, Dan Bentuk Musik - Mr. Suprijadi (SURYA SENI, 2008)
Batu Nisan Music Composition by FX Sutopo: Studied Based on the Aspect of the Mood, the Reference, and the Music Form. Batu Nisan is a complete masterpiece music composition composed by FX Sutopo in the form of orchestra and choir. It was composed in the unity of music form (Duchkomponirent).The process composistion went on for a year from 1962 to 1963 in Yogyakarta.The composition describes about  gravestone without identityfounded oudtside of resting place, and it was believed that the man burried under the gravestone was one of Indonesia independence heroes.The composition is worthy because of its creation concepts and historical background. To understand needs the Batu Nisan composition comprehensively, it needs to be studied by using qualitative method with the arstistic approach, and based on the three aspects of the Mood. the Reference, and the Music Form.Keywords: Batu Nisan, the Mood, the Reference, and the Music form.